The effect of tapered flow resistive loading inspiratory muscle training on respiratory function in post-stroke tracheostomy patients: study protocol for a parallel-group, assessor-blinded randomized controlled trial - Wang, Fuqiang; Li, Yaojiang; Deng, Yunhong; Huang, Congping; Li, Xiaodi; Fan, Kui; Deng, Lixia; Lv, Xiao (Frontiers in Neurology, 2025)
BackgroundPost-stroke tracheostomy patients frequently exhibit diverse levels of respiratory dysfunction. Inspiratory muscle training has demonstrated efficacy as an intervention to enhance respiratory function in these patients. However, conventional methods of inspiratory muscle training often fall short in terms of load regulation and individual adaptability. Tapered Flow Resistive Loading Inspiratory Muscle Training (TFRL-IMT) represents an innovative training modality that offers distinct advantages in augmenting respiratory muscle function. Nonetheless, its application in post-stroke tracheostomy patients remains under-researched, necessitating further systematic investigation to ascertain its clinical value.Methods and analysisThis investigation will employ a single-center, assessor-blinded, parallel-group randomized controlled trial design, enrolling 60 post-stroke tracheostomy patients (planned age range 18–70 years; and gender distribution will be collected and analyzed). Stratified compartmental group randomization will be utilized to allocate participants to either the experimental (n = 30) or control group (n = 30) in a 1:1 ratio. Both groups will receive conventional treatment, while the experimental group will additionally undergo TFRL-IMT using an electronic device that provides inspiratory resistance which dynamically decreases with increasing lung volume for a duration of three weeks. The primary outcome measure will be the rate of successful decannulation, with secondary outcomes encompassing diaphragm function, respiratory parameters, clinical outcomes, and quality of life assessments. The primary outcome (decannulation success rate) will be compared between groups using the Chi-square test.DiscussionTFRL-IMT may enhance respiratory function in patients through several mechanisms, including the provision of dynamic loading that aligns with the pressure-volume relationship of the respiratory muscles, the facilitation of neuromuscular adaptive changes, the optimization of the oxidative capacity of respiratory muscle fibers, and the remodeling of the central control pattern of the respiratory muscles. Nonetheless, the current study is subject to certain limitations, including its single-center design, a relatively short follow-up period, and some degree of device dependence and a high degree of heterogeneity in the stroke patient population.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2500097604.